2018
DOI: 10.4317/jced.55350
|View full text |Cite
|
Sign up to set email alerts
|

Aplasia of the lacrimal and major salivary glands (ALSG). First case report in spanish population and review of the literature

Abstract: Aplasia of the lacrimal and the major salivary glands (ALSG) is a rare disorder with scarce cases described in the recent literature. The pattern of genetic inheritance is autosomal dominant with variable expressivity. A 40 years male patient was referred to the Oral and Maxillofacial Service at the Hospital Universitario de A Coruña diagnosed with complete agenesis of all salivary glands. Our case it is the first of ALSG syndrome in the Spanish literature. Imaging tests are necessary to confirm the lack of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Incidental absence of the right submandibular gland in a 35-year-old woman, with a "mass" in the right sublingual space, has been reported in previous literature. 10,11 There were no associated calculi or other lesions, and the location of mass was above mylohyoid muscle sling. Their hypertrophy of the sublingual gland was seen in this instance.…”
Section: Discussionmentioning
confidence: 96%
“…Incidental absence of the right submandibular gland in a 35-year-old woman, with a "mass" in the right sublingual space, has been reported in previous literature. 10,11 There were no associated calculi or other lesions, and the location of mass was above mylohyoid muscle sling. Their hypertrophy of the sublingual gland was seen in this instance.…”
Section: Discussionmentioning
confidence: 96%
“…Salivary gland aplasia was first described in 1885 by Gruber [8]. Since then, only a few cases of aplasia, incomplete aplasia or hypoplasia have been reported in the literature [3,4,[9][10][11][12][13][14][15][16][17][18][19]. Pham Dang et al [16] in 2010 reported 35 cases of agenesis of the major salivary glands while in a more recent literature review by Kuralt et al [4], 148 radiologically confirmed cases of salivary gland aplasia were found; the median age of patients at the time of diagnosis was 21 years old and the majority were females (52.1%), as in our case who concerned a 23-year-old woman.…”
Section: Discussionmentioning
confidence: 99%